A severe predator-induced population decline predicted for endangered, migratory swift parrots (Lathamus discolor). (June 2015) - Heinsohn, Robert; Webb, Matthew; Lacy, Robert; Terauds, Aleks; Alderman, Rachael; Stojanovic, Dejan
Highlights: Introduced predators can severely impact endangered prey species. >50% of nesting female swift parrots are eaten by introduced sugar gliders. We modelled future decline using population viability analysis (PVA). Models projected a mean 86.9% decrease in swift parrots over 3 generations. PVAs effectively assess severe decline in species that are difficult to monitor. Abstract: Identifying the impact of introduced predators on endangered prey populations is critical for conservation management. Population viability analysis (PVA) becomes a valuable tool for quantifying such impacts when high quality life history data are available but, surprisingly, predictions from PVA of future population decline have seldom been used directly to assess conservation status. Here we synthesise new research on the unusual life history of the endangered swift parrot Lathamus discolor, an austral migrant that breeds in Tasmania, Australia. Swift parrots are challenging to monitor because (1) spatio-temporal fluctuation in food availability causes them to select entirely different breeding sites each year over a 10, 000 km 2 range, and (2) they suffer high but variable rates of predation from introduced sugar gliders Petaurus breviceps depending on where they breed. 50.9% of nesting females on the main island of Tasmania were killed by sugar gliders while incubating eggs, but there was no predation from this source on offshore islands. Over four years 16.5% (0–29%) of the population bred on offshore islands. We use PVAs to examine the likely extent of future population decrease due to sugar glider predation, and demonstrate that the remaining swift parrot population is likely to decrease by 78.8–94.7% (mean over four models = 86.9%) over only three generations (12–18 years). Our models offer a rare example of the use of PVAs for assessing impending population decline and conservation status in species that are challenging to monitor. In this case they support a change of status for swift parrots from "Endangered" to 'Critically Endangered' under IUCN criteria.